Ambiguous genitalia and hypertension in a patient with congenital adrenal hyperplasia. Issue 3 (27th February 2013) - Valsalan, R.; Zimmermann, A.
Abstract Congenital adrenal hyperplasia (CAH) is an uncommon condition. Its clinical presentation with hypertension is rare. Deficiency of the steroid 11‐beta‐hydroxylase accounts for less than 10% of CAH. We report a case of a 19‐year‐old patient who presents with hypertension with ambiguous genitalia secondary to adrenal steroidogenesis dysfunction. We also discuss the defects in adrenal steroidogenesis and clinical phenotypes of CAH.